Role of strategic planning, accounting information and advisors in the growth of small to medium enterprises / M. Christopher Catto - Catto, M. Christopher (Faculty of Accountancy, 2016)
This study explores the association between small to medium enterprise strategic planning, use of accounting information systems and role of accounting advisors in the growth of small to medium enterprises (SMEs). SMEs play a significant role in national economies worldwide. Research on SME growth and influence of management accounting on decision making is evolving. This study examines qualitative and quantitative data collected from 54 SMEs through a series of interviews held in conjunction with consultative programs. Contemporary SME life cycle literature, the use of accounting information and the implications of financial knowledge in the growth of small- to medium-sized businesses are considered. The study concludes with the proposition that central to the growth of SMEs is the embeddedness of knowledge into organisational motor cognition.